Hippocampal volume loss is associated with PET amyloid deposition in nondemented elderly individuals: Neuroimaging / Optimal neuroimaging measures for early detection. (7th December 2020) - Sathishkumar, Mithra; Larson, Myra S.; Taylor, Lisa; Keator, David; Hollearn, Martina K.; Miranda, Blake A.; Tustison, Nick; McMillan, Liv; Gillen, Daniel L.; Yassa, Michael A.
Abstract: Background: Amyloid‐beta (Aβ) plaques are among the hallmark pathologies of Alzheimer's disease (AD) and could potentially influence the aggregation of tau pathology, which is associated with neurodegeneration in AD. Prior work has demonstrated that left hippocampal atrophy is present in both Alzheimer's disease (AD) and mild cognitive impairment (MCI). However, these relationships are not clear in preclinical AD (i.e. those with Aβ biomarkers but no clinical impairment). This study assesses the relationship between Aβ pathology and hippocampal volume in nondemented older adults without clinical impairment. Method: Data from 54 adults (60‐85 years of age, 41 female) enrolled in the Biomarker Exploration for Aging, Cognition, and Neurodegeneration (BEACoN) study were included in this analysis. Participants underwent T1‐weighted MRI scans (MPRAGE) and PET amyloid scans with F18‐florbetapir (AV‐45) at the University of California, Irvine. Aβ status (+ or ‐) was determined by the composite score defined by Jack et al ( Alz Dem 2017). Each subject's T1 weighted MRI image was skull stripped and run through the joint label fusion (JLF) pipeline in ANTs to obtain medial temporal lobe subregion volumes and surface area. Cortical reconstruction was performed using Freesurfer 6.0 to obtain estimated total intracranial volume (ICV). All scans were then subjected to visual QC to ensure high quality segmentations. Of the sample of 54, 39 (29F) were Aβ‐ and 15 (12F) were Aβ+. We used two multiple regressions to determine if Aβ status was associated with left hippocampal volume. The first treated Aβ status as a binary variable and the second used the continuous SUVR measure in the AD composite region. Both models accounted for the effect of age and gender. Result: We found a significant association between left hippocampal volume and Aβ status, which remained significant after adjusting for age and gender. The result was further corroborated by using the continuous SUVR measures. Conclusion: Our results suggest that the association between amyloid deposition and hippocampal atrophy may begin years before the onset of Alzheimer's disease and can be detected even in nondemented older adults. Future work is needed to examine whether these relationships change longitudinally.